Islamic Parenting Education: Parenting Realizing The Golden Character of Alpha Generation - Saidek, Abdul Rahim; Rahmadoni, Jefril; Pramudya, Esen (Yayasan Sembilan Pemuda Indonesia, 2022)
This paper aims to provide an understanding of parenting style in order to realize the golden character of the alpha generation. The method used is literature. The findings show that in this increasingly sophisticated digital era, it has greatly influenced the mental development of the alpha generation which is very dependent on technology, many parents are negligent in supervising children, thus triggering children to commit deviant actions, for this reason, parents as educators The main role in the family must be able to educate and raise children to create good characters as early as possible. In the Qur'an there are many examples of parenting styles that have been applied by the prophet and previous people that can be applied today. Parenting styles that parents can adopt are authoritarian, democratic and permissive parenting styles.